The implementation process of knowledge management at the Institute of Radiation Protection and Dosimetry: actions and perspectives - Fernando Barcellos Razuck; Aucyone Augusto da Silva; Danielle Monegalha Rodrigues; Gisele Valente Cavalcante; Maria Elizabeth Dias Acar; Pamela Rodrigues Perrotta; Paulo Fernandes de Jesus; Maria Angelica Vergara Wasserman (Brazilian Journal of Radiation Sciences)
The Institute of Radiation Protection and Dosimetry (IRD) is a research and development institution, linked to the Brazilian Nuclear Energy Commission (CNEN), with a tradition of training human resources in the areas of radiation protection, dosimetry, medical physics and metrology of ionizing radiation. Despite this relevance, the IRD has suffered loss of its intellectual capital, mainly due to retirements and lack of replacement of qualified personnel. Thus, it is extremely important to preserve the technical-scientific knowledge related to its activities. A methodology that can help in this process is knowledge management (KM), in view of its potential to generate benefits in public and private organizations. Therefore, this work aims to carry out an experience report of the process of implementing KM at IRD, which used as a theoretical reference the models applied by the International Atomic Energy Agency (IAEA). Initial results include the creation of the working group on KM, the diagnosis of critical knowledge and maturity, the Knowledge Management Assistance Visit (KMAV) by IAEA and the production of papers. In addition, the support of the IRD's top management should be highlighted, which has made it possible to carry out activities related to the implementation and effectiveness of KM. Thus, it is intended to expand KM activities in the IRD, such as the execution of projects and the offer of training in the area.